Vaishnavi on Garuda - Temples of India Project Team (Jio Institute, 2024)
The foundation of the subsidiary shrine (II) on the left side corner in front of the Mahakal shrine reveals a sculpture of Vaishnavi who is shown seated on a garuda. The four-armed Vaishnavi is holding a shankha, gada, and chakra in her hands and one of her upper hands is damaged.